Characterization Of Kenaf Bast Fibre Filled Poly (Butylene Succinate) Composites: Mechanical, Water Absorption And Weathering Properties. - Ahmad Thirmizir, Mohd Zharif (2011)
Characterization of kenaf bast fibre (KBF) filled poly(butylene succinate) (PBS) composites in this study involved several stages. · Pencirian komposit poli(butilena suksinat) (PBS) terisi gentian kulit kenaf (KBF) ini melibatkan beberapa peringkat kajian